Paper Prototyping as a Rapid Participatory Design Technique. - Osman, Aznoora; Baharin, Hanif; Ismail, Mohammad Hafiz; Jusoff, Kamaruzaman (2009)
This paper describes participatory activities with university lecturers to design an online community. The objective of this study is to engage the users of an online community to collaboratively design their online community. We speculated that by involving them in the design team, we can identify their specific requirements, and they will accept and use the system. However, lecturers have heavy workload and tight schedule. For that reason, we thought that paper prototyping is the most suitable tool to be used because it is fast and easy to create. Therefore, paper prototyping technique has been adapted in a two-day participatory design session. We found that paper prototyping is indeed the most suitable technique to elicit requirements from the end users under a time constraint. Moreover, participants came out with unexpected requirements and novel interface.